Pengaruh Perputaran Kas, Piutang dan Persediaan Terhadap Profitabilitas Perusahaan Sektor Aneka Industri yang Terdaftar di BEI - Makatutu, Wiwin Samit; Arsyad, Rahma (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2021)
This study aimed to find out whether Cash Turnover, Receivable Turnover, and Inventory Turnover have positive and significant impact to Profitability and which variable has dominant effect to profitability in industry multi sector registered in Bursa Efek Indonesia. Profitability in this case means Return on Investment (ROI). The methodology used in this study is descriptive analysis, quantitative analysis and multiple regression analysis. From the statistic analysis, it is found that 1) the value of regression coefficient for Cash Turnover = 0,125 with significance value = 0,043, which means Cash Turnover has positive and significant impact on Profitability; 2) The value of Receivable Turnover = 0,292 with significance value = 0,017. This means that Receivable Turnover has positive and significant impact on Profitability; 3) the value of Inventory Turnover= 0,917 with significance value= 0,000. This shows that Inventory turnover has positive and significant impact to Profitability; 4) the variable which has the most effect on the Profitability in industry multi sector registered in BEI inventory turnover whose coefficient regression value is bigger compared to others, 0,917. Therefore, it can be conclude that all variable contribute positively and significantly to Profitability, and the dominant variable affected the Profitability is inventory turnover.